The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.vascn.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Integration and validation of the ex vivo human placenta perfusion model

Abstract: Based on the assessment of multiple quality control measurements, the described method of a closed human ex-vivo placenta perfusion model was validated. The success rate (38%) was more than twice the success rate reported in literature (15%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…On the one hand it has been demonstrated that placentas after vaginal delivery show increased oxidative stress and inflammatory cytokines on both gene-and protein levels (Cindrova-Davies et al, 2007). On the other hand, multiple studies showed no difference in placental barrier function during ex vivo perfusion for delivery mode (Mathiesen et al, 2010;Conings et al, 2017). Lastly, identified correlations should be cautiously interpreted due to the small sample size of the study, which also hampered correction for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand it has been demonstrated that placentas after vaginal delivery show increased oxidative stress and inflammatory cytokines on both gene-and protein levels (Cindrova-Davies et al, 2007). On the other hand, multiple studies showed no difference in placental barrier function during ex vivo perfusion for delivery mode (Mathiesen et al, 2010;Conings et al, 2017). Lastly, identified correlations should be cautiously interpreted due to the small sample size of the study, which also hampered correction for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo perfusion of human term placentae is used as a surrogate to study the transplacental transport of NPs. It is considered as the “gold standard” among currently available translocation models as it preserves the structural complexity of a full-term placenta and resembles its dynamic environment, enabling to study ex vivo transplacental NP passage without harming the mother and/or fetus [ 126 ]. Nonetheless, perfusion studies (i) predominantly use full-term placentae and, hence, do not allow to estimate NP transfer during earlier and more vulnerable stages of pregnancy, (ii) are limited to a few hours (4–8 h) of perfusion due to tissue degradation, which is insufficient to observe chronic effects, (iii) have a low success rate of perfusion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, perfusion studies (i) predominantly use full-term placentae and, hence, do not allow to estimate NP transfer during earlier and more vulnerable stages of pregnancy, (ii) are limited to a few hours (4–8 h) of perfusion due to tissue degradation, which is insufficient to observe chronic effects, (iii) have a low success rate of perfusion (i.e. , 30%), and (iv) are time-consuming [ 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, their location in a complex and rapidly evolving tissue has favored in situ investigations, which precluded functional studies. An ex vivo placental perfusion assay might be an alternative to study placental macrophages in their natural microenvironment [ 12 , 13 ]. However, despite its initial description some 50 years ago, placental perfusion assay has been mainly limited to pharmacological investigations [ 14 ].…”
Section: Placental Macrophage Investigation: Breaking Through the Barmentioning
confidence: 99%